To Be Good or To Be Better: Asset Managers' Attitudes Towards Herding - Torben Lütje (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
Based on a questionnaire survey the paper distinguishes between herding asset managers who try to be good and non-herding asset managers who try to be better than their competitors. It provides evidence for reputational herding and discusses herding managers' working effort, preferred sources of information and investment horizon. Additionally, their risk taking behavior including their investment behavior in short-term tournament scenarios is analyzed. It is found that herding managers assess themselves as generally more risk averse than non-herding managers, but in the tournament they are willing to take more risk. This finding is ascribable to their fear of falling out of the herd.
Keywords: G23; G14; 330; Institutional investors; herding; risk aversion; tournament hypothesis